1985
DOI: 10.1172/jci111852
|View full text |Cite
|
Sign up to set email alerts
|

Gamma interferon is spontaneously released by alveolar macrophages and lung T lymphocytes in patients with pulmonary sarcoidosis.

Abstract: Abstractosis may, at least in part, be due to suppression of IFN-y release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
231
0
3

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(253 citation statements)
references
References 50 publications
16
231
0
3
Order By: Relevance
“…In sarcoidosis, IFN-, TNF-and IL-1 have been reported to be increased in BALF cells and granulomatous lymph nodes in patients with sarcoidosis [4][5][6][7]. Prior & Haslam [32] showed elevated IFN-concentrations in sera of patients with pulmonary sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sarcoidosis, IFN-, TNF-and IL-1 have been reported to be increased in BALF cells and granulomatous lymph nodes in patients with sarcoidosis [4][5][6][7]. Prior & Haslam [32] showed elevated IFN-concentrations in sera of patients with pulmonary sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Excess synthesis of proinflammatory cytokines such as IL-1 , tumour necrosis factor-alpha (TNF-) and interferon-gamma (IFN-) has been found in bronchoalveolar lavage fluid (BALF) cells and granulomatous lymph nodes of patients with sarcoidosis [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA of 5 ϫ 10 6 cultured BAL fluid cells was isolated using Isogen (Nippon Gene, Toyama, Japan) and quantified by measurement of absorbance at 260 nm. To synthesize cDNA, 1 g of total RNA was incubated in the presence of Moloney murine leukemia virus reverse transcriptase (Life Technologies, Gaithersburg, MD) and 5 ng/ml oligo(dT) [12][13][14][15][16][17][18] primers (Pharmacia Biotech, Uppsala, Sweden) for 30 min at 42°C using reaction conditions described by the manufacturer (Life Technologies), and samples were stored at Ϫ80°C.…”
Section: Analysis Of Cytokine Gene Expressionmentioning
confidence: 99%
“…Many cytokines and chemokines play an important role during the processes of sarcoid granuloma (17). On the basis of recent Th1 and Th2 paradigms, the cytokine profile of sarcoidosis is Th1 dominant when disease activity is high (17)(18)(19). Recent studies have demonstrated enhanced expression of IL-12 (20 -22) and IL-12R (23,24) in sarcoid lungs.…”
mentioning
confidence: 99%
“…In order to understand this supposed mechanism in sarcoidosis, we therefore focused our work on critical cell surface receptors which bind exogenous stimuli [2][3][4]. It is well established that immunity-related receptors and proinflammatory cytokines, which include tumour necrosis factor (TNF)-α [5], interleukin (IL)-1 β [6], IL-2 [7], IL-6, IL-8 [8] and interferon (IFN)-γ [9], play a pivotal role in the formation of granulomas in sarcoidosis. The early phase in developing sarcoid granulomas is characterized by the accumulation and activation of T helper cells type 1 (Th1) lymphocytes, which lead to an immune response.…”
Section: Introductionmentioning
confidence: 99%